How does innovative continuous professional development (CPD) operate in the ECEC sector? Insights from a cross‐analysis of cases in Denmark, Italy and Poland. (22nd January 2018) - Bove, Chiara; Jensen, Bente; Wysłowska, Olga; Iannone, Rosa Lisa; Mantovani, Susanna; Karwowska‐Struczyk, Małgorzata
Abstract: This article offers insights into what characterises innovative continuous professional development (CPD) in the field of early childhood education and care (ECEC) by analysing similarities and differences from case studies of exemplary approaches to innovative CPD in Denmark, Italy and Poland. The comparative analysis focuses on four features that are particularly relevant for innovation in CPD in the field of ECEC: the social dimension of innovation as a strengthening component; the benefit of dynamic learning processes aimed at integrating theory and practice; the role of key figures in the quality of CPD; and measurements of CPD impact, outcomes and sustainability. This analysis sheds light on the effects of dynamic factors (e.g., regular team‐based reflection sessions based on documentation and observation), the importance of work conditions (e.g., contractual obligations to provide time for reflection), the critical role of pedagogical leaders (coordinators, principals and head teachers, supervisors), the importance of inter‐organisational networking at a local level and the facilitating role of collaboration with research institutes.